Rapid radio brightening of GRB 210702A - Anderson, Gemma; Russell, T D; Fausey, H M; van der Horst, A J; Hancock, P J; Bahramian, A; Bell, M E; Miller-Jones, J C A; Rowell, G; Sammons, M W; Wijers, R A M J; Galvin, T J; et al. (Monthly notices of the Royal Astronomical Society, 2023)
We observed the rapid radio brightening of GRB 210702A with the Australia Telescope Compact Array (ATCA) just 11 h post-burst, tracking early-time radio variability over a 5 h period on ∼15 min time-scales at 9.0, 16.7, and 21.2 GHz. A broken power law fit to the 9.0 GHz light curve showed that the 5 h flare peaked at a flux density of 0.4 ± 0.1 mJy at ∼13 h post-burst. The observed temporal and spectral evolution is not expected in the standard internal-external shock model, where forward and reverse shock radio emission evolves on much longer time-scales. The early-time (<1 d) optical and X-ray light curves from the Neil Gehrels Swift Observatory demonstrated typical afterglow forward shock behaviour, allowing us to use blast wave physics to determine a likely homogeneous circumburst medium and an emitting electron population power-law index of p = 2.9 ± 0.1. We suggest that the early-time radio flare is likely due to weak interstellar scintillation (ISS), which boosted the radio afterglow emission above the ATCA sensitivity limit on minute time-scales. Using relations for ISS in the weak regime, we were able to place an upper limit on the size of the blast wave of ≲6 × 1016 cm in the plane of the sky, which is consistent with the theoretical forward shock size prediction of 8 × 1016 cm for GRB 210702A at ∼13 h post-burst. This represents the earliest ISS size constraint on a gamma-ray burst (GRB) blast wave to date, demonstrating the importance of rapid (<1 d) radio follow-up of GRBs using several-hour integrations to capture the early afterglow evolution and to track the scintillation over a broad frequency range.